Lesbian Fetishism? Лезбејски фетишизам? - Grosz, Elizabeth; Trajanoski, Žarko (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Elizabeth Grosz | Елизабет Грос Title (English): Lesbian Fetishism? Title (Macedonian): Лезбејски фетишизам? Translated by (English to Macedonian): Žarko Trajanoski | Жарко Трајаноски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 113-134 Page Count: 21 Citation (English): Elizabeth Grosz, “Lesbian Fetishism?,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 113-134. Citation (Macedonian): Елизабет Грос, „Лезбејски фетишизам?“, превод од англиски Жарко Трајаноски, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 113-134.